Phytohormone profiles and related gene expressions after endodormancy release in developing Pinus tabuliformis male strobili. (March 2022) - Zhang, Jing-Xing; Liu, Hong-Mei; Yang, Bo-Ning; Wang, Hui-Li; Niu, Shi-Hui; El-Kassaby, Yousry A.; Li, Wei
Highlights: The network of hormones regulated the growth of Pinus tabuliformis male strobili after endo-dormancy release was contributed. ABA was screened out as the key hormone in developing Pinus tabuliformis male strobili after endo-dormancy release. HAB2-SNRK2.10 was identified as the core module of hormone network in male strobili development after endodormancy release. Abstract: Development after endo-dormancy release ensures perennial plants, such as forest trees, proper response to environmental changes and enhances their adaptability. In northern hemisphere, megasporophore and microsporophore of conifers undergo dormancy to complete their development. Here combined with transcriptome data, we used high-performance liquid chromatography/electrospray ionization tandem mass spectrometry (ESI-HPLC-MS/MS) to quantitatively analyse the various hormones (Abscisic Acid (ABA), 3-Indoleacetic acid (IAA), Gibberellins (GAs), Cytokinin (CTK), Jasmonic acid (JA) and Salicylic acid (SA)) of Chinese pine ( Pinus tabuliformis Carr. ) male strobili after endo-dormancy release. More specifically, we analysed endogenous hormones and their related-genes and verified the important role of ABA in plants growth and development. We observed rapid decrease in ABA content after dormancy release, resulting in reducing the inhibitory effect on male strobili growth. Similarly, rapid drop in ABA/GA ratio was observed and was associated with the start of male strobili growth and development. Combined with transcriptome data, we found that HAB2-SnRK2.10 played a central role in the ABA pathway in the entire network of hormones regulating male strobili development. Due to external environment warming, the differentially expressed HAB2-SnRK gene led to ABA content rapid decline, thus initiating male strobili growth. We constructed a network of hormone-regulated development to understand the interactions between hormones after male strobili dormancy release of male strobili. This study provided essential foundations for studying megasporophore and microsporophore growth mechanism after endo-dormancy and offered new ideas for flower development in gymnosperms and angiosperms.